POOR KNOWLEDGE BUT GOOD ATTITUDE TOWARDS ANABOLIC ANDROGENIC STEROIDS AMONG STUDENTS IN A LOCAL TERTIARY INSTITUTION - Han, Kang Waye; Chih, Ling Wei; Yee, Loo Min; Min, Leong Xue; Fan, Ooi Yi; Qi, Teo Wen; Jun, Neoh Teng (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Non-medical use of anabolic androgenic steroids (AAS) is a widespread public health concern, with up to 8% of university students using it for aesthetic purposes. Studies have reported poor knowledge and attitude towards AAS among university students. Our study aims to study the knowledge and attitude on AAS among male undergraduate students in University Tunku Abdul Rahman (UTAR). METHODOLOGY One thousand three hundred eight (1308) male university students were recruited via convenience sampling and given an online self-administering questionnaire between December 2021 – February 2022. The questionnaire documented their socio-demographic parameters, as well as assessed their knowledge and attitude towards AAS. RESULTS 68.6% of our respondents had poor knowledge on AAS; students from the urban campus or those who spent >30 minutes in the gym had significantly higher knowledge. Interestingly, the level of knowledge on AAS was lower among students who participated in competitive sports. Most of the students were not aware that AAS abuse may affect their mental health or even result in other complications such as gynaecomastia. On the contrary, 83% of the students had a good attitude towards AAS. There was a significant association between family history of AAS use and poorer attitude. Most of the students (79.1%) admitted they would not use AAS in the future, while only 7.7% agreed that AAS should be used freely among athletes. Only 35% agreed that the public should be allowed access to AAS under medical supervision. There is a significant but mild positive correlation between the knowledge scores and attitude scores among the participants. CONCLUSION Our study is the first in Malaysia that depicts poor knowledge but good attitude of male university students towards AAS. Hence, there is a need for university students to be exposed to information regarding AAS abuse and its complications.